1984
DOI: 10.1063/1.94583
|View full text |Cite
|
Sign up to set email alerts
|

Polyimide passivation of In0.53Ga0.47As, InP, and InGaAsP/InP p-n junction structures

Abstract: Techniques for passivating In0.53Ga0.47As, InGaAsP, InP, and InGaAsP/InP p-n junction structures with polyimide have been developed. Low stable leakage current is maintained for prolonged bias, even after exposure to high temperatures (∼320 °C) during packaging. 150-μm-diam In0.53Ga0.47As photodiodes with a breakdown voltage of ∼50 V were passivated with polyimide and were found to consistently have leakage currents of ∼10 nA at a 20-V bias.Details of the passivation process are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…After imidization, however, they have properties that inhibit processability, insolubility, intractability, and high glass transition temperature. [1][2][3][4] In the last decade, several copolyimides containing polyorganosiloxane in their copolymer backbone, as block units, have been prepared to improve processing, and they have been applied in high-performance adhesives and special coatings. [5][6][7][8] Recently, some copolyimides containing polyorganofluorosiloxane have been reported that exhibit low dielectric constants.…”
Section: Introductionmentioning
confidence: 99%
“…After imidization, however, they have properties that inhibit processability, insolubility, intractability, and high glass transition temperature. [1][2][3][4] In the last decade, several copolyimides containing polyorganosiloxane in their copolymer backbone, as block units, have been prepared to improve processing, and they have been applied in high-performance adhesives and special coatings. [5][6][7][8] Recently, some copolyimides containing polyorganofluorosiloxane have been reported that exhibit low dielectric constants.…”
Section: Introductionmentioning
confidence: 99%
“…In order to optimize the dark current performance, many methods including post pixel processing passivation and various epilayer designs have been developed, but none of these techniques have fully eliminated the leakage at the surface [6][7][8][9][10][11][12]. Relatively recently, barrier structured detectors have been numerically and experimentally shown to produce lower dark current than conventional pn junction detectors and to operate at higher operation temperatures .…”
Section: Introductionmentioning
confidence: 99%
“…Also, PI physically passivates and protects the semiconductor surfaces from the ambient environment while maintaining or even improving the electrical performance of the device measured prior to passivation. A number of groups have reported on the passivating behavior of PI in InGaAs/InP [3,4,5].…”
Section: Introductionmentioning
confidence: 99%